Bioaugmentation with Clostridium thermocellum to enhance the anaerobic biodegradation of lignocellulosic agricultural residues. (February 2018) - Ecem Öner, Büşra; Akyol, Çağrı; Bozan, Mahir; Ince, Orhan; Aydin, Sevcan; Ince, Bahar
Highlights: Bioaugmentation with C. thermocellum at different inoculation ratios was assessed. Methane yield was increased up to 39% at the inoculation ratio of 20% (v:v). Firmicutes, Thermotogae and Bacteroidetes were the most abundant phyla. 44% higher abundance of Ruminococcaceae was observed comparing to the control. Methanomicrobia, played a crucial role during the biomethanation. Abstract: This study aimed to improve biomethane production from lignocellulosic biomass by assessing the impact of bioaugmentation with Clostridium thermocellum on the performance of anaerobic digesters at different inoculation ratios. The outputs of the digestion experiments revealed that bioaugmentation strategies with C. thermocellum increased the methane yield up to 39%. The sequencing analysis indicated that the indigenous microbial community was modified by the bioaugmentation. During the process of bioaugmentation, in the digester that was inoculated at the ratio of 20% (v:v), an increase in the abundance of Ruminococcaceae family led to a decrease in the Bacteroidaceae and Synergistaceae families. Furthermore, the metabolic products of the bioaugmented strains greatly influenced the diversity of the archaeal community and an increase in the abundance of Methanomicrobiales was observed.